2020
DOI: 10.1038/s41598-020-62948-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemical manipulation of hydrogen induced high p-type and n-type conductivity in Ga2O3

Abstract: Advancement of optoelectronic and high-power devices is tied to the development of wide band gap materials with excellent transport properties. However, bipolar doping (n-type and p-type doping) and realizing high carrier density while maintaining good mobility have been big challenges in wide band gap materials. Here P-type and n-type conductivity was introduced in β-Ga2O3, an ultra-wide band gap oxide, by controlling hydrogen incorporation in the lattice without further doping. Hydrogen induced a 9-order of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 52 publications
2
47
0
Order By: Relevance
“…What is the identity of these bright, localized emitters? Prior work has shown that hydrogen diffuses into Ga 2 O 3 and increases its conductivity 35 . Annealing in a reducing atmosphere such as hydrogen also decomposes the surface and may result in Ga-rich pits.…”
Section: Resultsmentioning
confidence: 99%
“…What is the identity of these bright, localized emitters? Prior work has shown that hydrogen diffuses into Ga 2 O 3 and increases its conductivity 35 . Annealing in a reducing atmosphere such as hydrogen also decomposes the surface and may result in Ga-rich pits.…”
Section: Resultsmentioning
confidence: 99%
“…Thanks to these properties, positron annihilation methods have been successful in identifying the role of native point defects in the electrical compensation of n-type doped compound semiconductors such as GaN, ZnO, AlN, InN, and In 2 O 3 [12][13][14][15][16], as well as their alloys such as InGaN and AlGaN [17][18][19][20][21][22]. In spite of the otherwise significant research interest in β-Ga 2 O 3 , the number of reported studies with positron annihilation is surprisingly low [23][24][25][26]. These studies suggest that cation vacancies contribute to the compensation of n-type conductivity, but also point out a potential difficulty in interpreting the positron annihilation signals.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of this value with the values listed in TableI suggest that V ib Ga 2H and V Ga(2) H-V O(2), which are the lowest energy configurations for V Ga 2H and V Ga H−V O -type defects, respectively, are excellent candidates for the filled trap. The E b 's of V ib Ga 3H and V ib Ga 4H, which were recently shown 57 to be more likely than the corresponding structures consisting of unshifted V Ga(1) ,31 are considerably lower than our experimental E b , and are 10 This is the author's peer reviewed, accepted manuscript. However, the online version of record will be different from this version once it has been copyedited and typeset.…”
mentioning
confidence: 50%